Organizational Identity Formation in Alternative Organizations: A Study of Three Benefit Corporations. (November 2019) - Kopaneva, Irina M.; Cheney, George
The benefit corporation (BC) in the United States is a new type of corporation legally required to generate profit for its shareholders and to pursue public benefit. BCs explicitly work to balance profit maximization and social mission, which is an ongoing challenge for businesses with an expansive view of the bottom line. This multiple case study extends scholarship on identity formation (IF) in nontraditional organizations, such as BCs, by providing empirical evidence of how identities develop in relation to prevailing cultural sentiments. In particular, we demonstrate how BC struggles over organizational identity (OI) reference broader socioeconomic discourses, identify mechanisms through which perceived pressures suppress alternative interpretations of OI at a micro-level of member interaction, and expose tensions between dominant and alternative frames for business enterprise.